2011
DOI: 10.1074/jbc.m111.236281
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin, a Flavone, Induces the Differentiation of Cultured Osteoblasts

Abstract: Flavonoids, a group of natural compounds found in a variety of vegetables and herbal medicines, have been intensively reported on regarding their estrogen-like activities and particularly their ability to affect bone metabolism. Here, different subclasses of flavonoids were screened for their osteogenic properties by measuring alkaline phosphatase activity in cultured rat osteoblasts. The flavone baicalin derived mainly from the roots of Scutellaria baicalensis showed the strongest induction of alkaline phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…Taken together, these results suggested that the osteogenic effects mediated by flavonoids could be dependent or independent of their estrogenic properties. This idea is supported by our previous screening of different flavonoids, encompassing the major sub-classes, which showed that the estrogenic activities of selective flavonoids are not correlated with osteogenic activities [12]. Moreover, our results also implied that different flavonoids could promote bone differentiation via different signaling mechanisms and these mechanisms of action and signaling cascades should be further studied.…”
Section: Resultssupporting
confidence: 81%
“…Taken together, these results suggested that the osteogenic effects mediated by flavonoids could be dependent or independent of their estrogenic properties. This idea is supported by our previous screening of different flavonoids, encompassing the major sub-classes, which showed that the estrogenic activities of selective flavonoids are not correlated with osteogenic activities [12]. Moreover, our results also implied that different flavonoids could promote bone differentiation via different signaling mechanisms and these mechanisms of action and signaling cascades should be further studied.…”
Section: Resultssupporting
confidence: 81%
“…These compounds can be divided into 6 categories, including flavonoids: icariin (Figure 1) [2326], genistein (Figure 2) [29], daidzein (Figure 2) [31, 32], kaempferol (Figure 11) [72], quercetin (Figure 11) [73, 74], naringin (Figure 8) [75–77], hesperidin (Figure 11) [78], linarin (Figure 11) [79], bavachalcone (Figure 3) [36], rutin (Figure 11) [80], (+)-catechin (Figure 11) [81], nobiletin (Figure 11) [82], luteolin (Figure 11) [83], baicalein (Figure 11) [84], baicalin (Figure 1) [85], xanthohumol (Figure 11) [86]; coumarins: psoralen (Figure 3) [35], osthole (Figure 11) [87]; lignans: honokiol (Figure 11) [88, 89], isotaxiresinol (Figure 11) [90], magnolol (Figure 11) [91]; polyphenol: resveratrol (Figure 11) [9295], curcumin (Figure 11) [9698], tea polyphenols (including epigallocatechin-3-gallate, epigallocatechin, epi-catechin, epicatechin-3-gallate, Figure 11) [99, 100]; anthraquinones: rubiadin (Figure 10), 2-hydroxy-1-methoxy-anthraquinone (Figure 10), 1,3,8-trihydroxy-2-methoxy-anthraquinone (Figure 10) [71]; alkaloids: harmine (Figure 11) [101], coptisine (Figure 11) [102], palmatine (Figure 11) [103], berberine (Figure 11) [104, 105]; and other compounds: curculigoside (Figure 11) [106, 107], asperosaponin VI (Figure 11) [108], limonoid 7-oxo-deacetoxygeduni...…”
Section: Resultsmentioning
confidence: 99%
“…In line to this notion, a study showed that ER α played a critical role in estrogen-induced glutamatergic synapse formation, including the expressions of presynaptic vesicular glutamate transporter protein (vGlut1) and postsynaptic NMDA receptor (NR1 subunit) [37]. Flavonoids are well-known phytoestrogens with multiple activities in different systems [38, 39]. Much attention has been focused on the neuronal beneficial effects of flavonoids, including the neuroprotection against neurotoxin stress [16] as well as the promotion of memory and learning and cognitive functions [15].…”
Section: Discussionmentioning
confidence: 99%